Class and inequality in the United States - Berberoglu, Berch (Emerald Publishing Limited, 2024)
At a time of growing wealth and income inequality in the United States during recent decades, Class and Inequality in the United States examines the nature and sources of social inequality based on class, race, and gender relations throughout the course of U.S. history. Addressing the class bases of social inequality during the turbulent 20th and early 21st centuries, Berch Berberoglu stresses the urgency of the study of class relations and their contradictory and unequal outcomes in American society today. Exploring the development of class-consciousness and class struggles of working people, Class and Inequality in the United States examines the realities behind conflicting class relations, the effects of racial and gender oppression, and the dynamics of social change through struggles between the contending class forces that have shaped the contours of contemporary American society and will continue to affect the course of its development in the coming decades. Highlighting not only the severity of social problems resulting from class-based inequalities, but also the need to find solutions for current problems in American society moving forward, Berberoglu provides a captivating read for anyone interested in understanding how working people today can have a lasting impact on combatting inequalities in the United States for a better and more equitable society in the future.
Includes index.
Keywords: Equality -- United States.; Social Science / Social Classes & Economic Disparity.; Social discrimination and social justice.; Social classes.; elektronické knihy; electronic books